2022
DOI: 10.3390/antibiotics11081021
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring of Mycoplasma gallisepticum Minimum Inhibitory Concentrations during the Last Decade (2010–2020) Seems to Reveal a Comeback of Susceptibility to Macrolides, Tiamulin, and Lincomycin

Abstract: Mycoplasma gallisepticum (Mg) is a highly contagious avian pathogen responsible for significant economic losses for the poultry industry. In some circumstances, antimicrobial treatment is useful to contain clinical signs of Mg infection in birds. However, antimicrobial resistance emergence is now common among animal pathogens, becoming a worldwide health concern. The collection of minimum inhibitory concentration (MIC) data is fundamental for an appropriate antimicrobial use and for fighting antimicrobial resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…The same study found four isolates with a higher MIC value of 1 mg × L −1 . The MIC value of 2 mg × L −1 was registered in another study [44]. These data confirm that doxycycline can be effective against M. gallisepticum and also indicate that it is advisable to use the tetracycline antibiotic in practice after the antimicrobial susceptibility test.…”
Section: Discussionsupporting
confidence: 61%
“…The same study found four isolates with a higher MIC value of 1 mg × L −1 . The MIC value of 2 mg × L −1 was registered in another study [44]. These data confirm that doxycycline can be effective against M. gallisepticum and also indicate that it is advisable to use the tetracycline antibiotic in practice after the antimicrobial susceptibility test.…”
Section: Discussionsupporting
confidence: 61%
“…The level of lincomycin in the liver has medicinal value in all groups, indicating the long-term persistence of the drug in the liver. Table-3 [ 12 , 13 , 17 , 18 , 34 , 35 ] compares the drug levels in broiler tissues with the MIC values of lincomycin from recent studies. Several antimicrobial drugs, such as tetracycline [ 25 ], enrofloxacin [ 36 ], florfenicol [ 37 ], and tilmicosin [ 38 ], have been reported to have higher doses in the liver than in the muscle or kidney of broilers.…”
Section: Discussionmentioning
confidence: 99%